Sarcopenia in Patients With Parkinson's Disease: A Systematic Review and Meta-Analysis - Cai, Yingying; Feng, Fei; Wei, Qianqian; Jiang, Zheng; Ou, Ruwei; Shang, Huifang (Frontiers in Neurology, 2021)
Background: Parkinson’s Disease (PD) and sarcopenia are two common diseases in aging people. To date, the prevalence of sarcopenia in PD patients and the relationship between clinical features and sarcopenia in PD patients are not clear. The aim of the study was to 1) assess the prevalence of sarcopenia in PD patients; 2) reveal the clinical features between PD patients with and without sarcopenia. Method: A systematic review was carried out through screening PubMed, EMBASE and Cochrane database in May 2020 to identify. All study designs (case-control, cohort and cross-sectional studies) were eligible for the meta-analysis. Data of patients’ characteristics, sarcopenia criteria, sarcopenia prevalence, sarcopenia measures were retrieved. The primary outcome was estimated prevalence of sarcopenia by a pooled prevalence (%) and its 95% confidence interval (CI), using a random effect model. The secondary outcome was the differences in clinical features between PD patients with and without sarcopenia by meta-analysis. Included articles were assessed for risk of bias. Potential sources of variation were investigated by using subgroup analyses and meta-regression. Result: Ten studies were included in the review. Among them, 9 were cross-sectional studies and 1 was a prospective cohort study. Age of participants with PD in the studies ranged from 51.1 to 80.7 years. The estimated prevalence of sarcopenia ranged from 6% to 55.5%. The random-effects pooled prevalence was 29% (95% confidence intervals: 0.18 - 0.40). When only studies at low risk of bias were considered, pooled prevalence decreased to 17% (95% confidence intervals: 0.02 - 0.33), with still high heterogeneity. The incidence of falls in PD patients with sarcopenia was higher than that in PD patients without sarcopenia. There was no difference in sex ratio between PD patients with and without sarcopenia. Conclusion: Sarcopenia seems to be common in patients with PD. Early assessment of sarcopenia should be implemented in PD to avoid fall and disability.